Optimum design, simulation and test of a new flow control valve with an electronic actuator for turbine engine fuel control system. (March 2019) - Mojallal Agh, Seyfoddin; Pirkandi, Jamasb; Mahmoodi, Mostafa; Jahromi, Mehdi
Abstract: This paper presents the design and experimental implementation of a new rotary proportional flow control valve. This valve is equipped with a needle valve for fine adjusting and a plunger type adjustable pressure compensating valve to retaining constant pressure difference across it. The plunger in flow control valve is directly coupled to an electronic servomotor as a rotary actuator. The modified new opening shape of the flow metering area is two trapezoids with fixed height and variable base. This area forms by the intersection of two triangle ports on the sleeve and two rectangular ports on the plunger. This configuration is used as a flow metering unit in a gas turbine engine fuel control system. The output metered flow is proportional to the flow control valve's angular position and it is not sensitive to pressure variations across the valve. Because of linear relation between the output fuel flow and valve position (throttle position), this unit is used as a variable area fuel flow meter device in engine control system. The aim of this new design is to change and modify a manual fuel control unit with a set point and to develop a throttleable electrohydraulic fuel control system for more precise control of a turbine engine at high altitudes. The main innovations in the present fuel metering unit include the modified and new design of the rotary valve opening shape(s), use of a rotary electronic actuating mechanism and also direct coupling of the actuator and the flow control valve with a simple spline coupling. Using the direct drive actuation of flow control valve, instead of the more common hydro mechanical mechanisms, has reduced the number of parts. And made the whole system lighter and cut down on the manufacturing cost. The increased fuel metering precision in the new flow control valve has increased the ultimate control accuracy of the system. In order to acquire the optimal design parameters, the proposed system has been modeled and simulated for different operating conditions. After manufacturing a prototype of the unit, it has been tested on a special test rig. To validate the model, the test results has been compared with the simulation results. This comparison shows the maximum deviation of about 4% between the simulation results and empirical tests. Highlights: Research on characteristics of a new rotary proportional flow control valve. Proposal of using flow control valves with new trapezoids opening shape. Derivation of simulations in Matlab and verified experimentally on a test bench. Proposing a modified rotary direct drive proportional valve for fuel control systems. A novel flow control valves actuation system in gas turbine fuel control units.